Preparation method of lithium disilicate glass ceramic with layered gradient transparency and color

CN119330601APending Publication Date: 2025-01-21LINGJIU INNOVATION (SICHUAN) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411548028.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing lithium disilicate glass ceramics cannot achieve the effect of gradually increasing transparency from the neck edge to the cut end and gradually becoming lighter in color, resulting in cumbersome denture processing processes and the risk of porcelain layer collapse.

Method used

By performing the thermal treatment of the first heating area and the second heating area on the basic glass plate, heat treatment of the glass plate from the surface of the two sides, and then gradually stop the heating, forming a dilateral silicon glass with a layered and colorful color of the color. ceramics.

Benefits of technology

In the case of realizing that the transparent porcelain is not required, the cutting end of the denture is higher and the color becomes lighter. From the edge of the neck to the end, it forms a natural gradient effect, which enhances the aesthetic repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330601A_ABST
    Figure CN119330601A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of lithium disilicate glass ceramic with layered gradient transparency and color, and belongs to the technical field of lithium silicate glass. The preparation method comprises the following steps of ingredient melting, forming, annealing, heat treatment and the like. After base glass is prepared, the base glass plate is subjected to heat treatment in the directions of the surfaces of the two sides of the base glass plate through a first heating area and a second heating area, and then heating is stopped in the first heating area and the second heating area in sequence; the crystal growth size of one surface, which is not heated, on the basic glass plate is larger, the crystallinity is higher, and the surface is more transparent without stacking plastic cutting end transparent porcelain after being finally processed into a false tooth, and is comparable with the cutting end permeability of natural teeth; meanwhile, due to the fact that the transparency is increased, the color of the cut end becomes light, and finally the natural gradual change effect that the transparency is continuously increased and the color becomes light continuously from the neck edge to the cut end is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium silicate glass, and in particular to a method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color. Background Art

[0002] Lithium disilicate glass-ceramic, as an oral denture restoration material, is widely favored by the world because of its excellent aesthetic restoration effect and bionic properties that are closest to natural teeth.

[0003] At present, most of the lithium disilicate glass ceramics on the market are produced by the process of glass liquid melting-mold forming-annealing-heat treatment, and the product color and transparency are uniform. However, due to the overall uniformity of lithium disilicate glass ceramics, it is impossible to achieve the effect of natural teeth gradually increasing transparency and gradually lightening color from the cervical edge to the incisal edge. Therefore, when using it, technicians need to pile up transparent porcelain on the incisal end to increase the transparency of the incisal end in order to meet the requirements of aesthetic restoration. This also makes the processing of dentures more complicated, and there is also a risk of porcelain layer collapse. Summary of the invention

[0004] The present invention is to solve the problem that the existing lithium disilicate glass ceramics cannot achieve the effect of natural teeth gradually increasing transparency and gradually lightening color from the cervical edge to the incisal edge, and provide a preparation method of lithium disilicate glass ceramics with gradual transparency and color changes. After the base glass is prepared, the present invention then heat treats the base glass plate from the surface directions of both sides of the base glass plate through the first heating zone and the second heating zone respectively, and then the first heating zone and the second heating zone stop heating successively; the crystal growth size of the side of the base glass plate that stops heating later is larger and the crystallinity is higher, and finally after being processed into a denture, the transparent porcelain of the incisal edge will be more transparent without the need for stacking, comparable to the transparency of the incisal edge of natural teeth; at the same time, because the transparency increases, the color of the incisal edge will become lighter, and finally a natural gradient effect of increasing transparency and lightening color from the cervical edge to the incisal edge is formed.

[0005] The technical solution adopted by the present invention is:

[0006] A method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color, comprising the following steps:

[0007] Step S1, weighing raw materials according to the ratio, mixing them evenly and then melting them at high temperature to obtain homogeneous glass liquid;

[0008] Step S2, pouring the glass liquid into a preheated forming mold and cooling it to obtain a basic glass plate;

[0009] Step S3, placing the base glass plate in an annealing furnace for annealing treatment;

[0010] Step S4, using the annealed base glass plate as a physical partition between the first heating zone and the second heating zone, and heat-treating the base glass plate from the two side surfaces of the base glass plate by the first heating zone and the second heating zone respectively, and then stopping heating in the first heating zone and the second heating zone successively to obtain lithium disilicate glass ceramics with layered gradient transparency and color.

[0011] Furthermore, the chemical composition of the lithium disilicate glass-ceramic obtained in the step S4 is: SiO2, 65~75wt%, Li2O, 13~15wt%, Al2O3, 2~5wt%, K2O, 0.1~4wt%, Na2O, 0.1~4wt%, P2O5, 2~5wt%, TiO2, 1~4wt%, F, 0.5~3wt%, CeO2, 0.5~2wt%, Er2O3, 0.1~5wt%, MnO2, 0.1~1wt%.

[0012] Furthermore, the temperature of the high temperature melting in step S1 is 1350-1450° C., and the temperature is kept for 1-4 hours.

[0013] Furthermore, the preheating temperature of the molding die in step S2 is 100-800°C.

[0014] Furthermore, the specific process of the annealing treatment in step S3 is: keeping warm in a furnace at 520-650°C for 0.5-2h; then heating to 720-780°C at ≤5°C / min, keeping warm for 0.5-4h; then heating to 820-850°C at ≤5°C / min, keeping warm for 0.5-2h; then heating to 900-920°C at 15-20°C / min, keeping warm for 0.5-1h; then cooling to 520-650°C at 15-20°C / min, keeping warm for 0.5-2h; finally cooling to below 100°C at 15-20°C / min and taking out of the furnace.

[0015] Furthermore, in the step S4, when the first heating zone and the second heating zone perform heat treatment on the base glass plate from the two side surfaces of the base glass plate respectively, the temperatures of the first heating zone and the second heating zone are first raised to the same preset temperature and kept warm; then the first heating zone stops heating and cools naturally, while the second heating zone continues to keep warm; finally, the second heating zone stops heating and cools naturally;

[0016] Alternatively, when the first heating zone and the second heating zone perform heat treatment on the base glass plate from the two side surfaces of the base glass plate in step S4, the temperatures of the first heating zone and the second heating zone are first increased to the same preset temperature and kept warm; then the second heating zone stops heating and cools naturally, while the first heating zone continues to keep warm; finally, the first heating zone stops heating and cools naturally.

[0017] Furthermore, in step S4, the temperatures of the first heating zone and the second heating zone are raised to 510-720° C. and kept warm for 1-3 hours; then the second heating zone stops heating, while the first heating zone continues to keep warm for 30-60 minutes before stopping heating.

[0018] Furthermore, in step S4, the temperature of the first heating zone and the second heating zone is first increased to 510-550° C. and kept for 1-2 hours; and then increased to 600-720° C. and kept for 10-60 minutes.

[0019] Furthermore, in step S4, the temperatures of the first heating zone and the second heating zone are raised to 510-720° C. and kept warm for 1-3 hours; then the first heating zone stops heating, while the second heating zone continues to keep warm for 30-60 minutes before stopping heating.

[0020] Furthermore, in step S4, the temperature of the first heating zone and the second heating zone is first increased to 510-550° C. and kept for 1-2 hours; and then increased to 600-720° C. and kept for 10-60 minutes.

[0021] The beneficial effects of the present invention are:

[0022] The present invention is to solve the problem that the existing lithium disilicate glass ceramics cannot achieve the effect of natural teeth gradually increasing transparency and gradually lightening color from the cervical edge to the incisal edge, and provide a preparation method of lithium disilicate glass ceramics with gradual transparency and color changes. In the preparation method, after the base glass is prepared, the base glass plate is heat-treated from the surface directions of both sides of the base glass plate through the first heating zone and the second heating zone respectively, and then the first heating zone and the second heating zone stop heating successively. The crystal growth size of the side of the base glass plate that stops heating last is larger and the crystallinity is higher. Finally, after being processed into a denture, the transparent porcelain of the incisal end will be more transparent without the need for stacking, which is comparable to the transparency of the incisal end of natural teeth; at the same time, because the transparency increases, the color of the incisal end will become lighter, and finally a natural gradient effect of increasing transparency and lightening color from the cervical edge to the incisal end is formed. At the same time, the present invention can control the transparency and color of the upper surface by adjusting the heat preservation time of the heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is the XRD test result of the lithium disilicate glass ceramic prepared in Example 1.

[0025] Figure 2 This is the appearance of the denture prepared in Example 6.

[0026] Figure 3 This is the SEM test result of the incisal end of the denture prepared in Example 6.

[0027] Figure 4 This is the SEM test result of the cervical edge of the denture prepared in Example 6. DETAILED DESCRIPTION

[0028] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0029] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention.

[0030] The embodiments of the invention are described in detail below with reference to the accompanying drawings.

[0031] Example 1

[0032] A method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color, comprising the following steps:

[0033] Step S1, weighing raw materials according to the ratio, mixing them evenly, melting them at a high temperature of 1400°C, and keeping them warm for 2 hours to obtain a homogeneous glass liquid; wherein the raw materials are composed of: 56.08wt% of quartz sand, 28.29wt% of lithium carbonate, 4.22wt% of aluminum hydroxide, 1.16wt% of potassium carbonate, 1.28wt% of sodium carbonate, 4.99wt% of diammonium phosphate, 0.79wt% of titanium dioxide, 1.62wt% of sodium fluorosilicate, 0.63wt% of cerium oxide, 0.86wt% of erbium oxide, and 0.08wt% of manganese dioxide.

[0034] Step S2, preheating the forming mold to 200°C, pouring the glass liquid into the preheated forming mold, and cooling to obtain a basic glass plate.

[0035] Step S3, placing the base glass plate in an annealing furnace for annealing treatment. The specific process of annealing treatment is: keep the temperature in the furnace at 590℃ for 1 hour; then increase the temperature to 750℃ at 3℃ / min and keep it for 2.5 hours; then increase the temperature to 830℃ at 3℃ / min and keep it for 1.5 hours; then increase the temperature to 910℃ at 15℃ / min and keep it for 1 hour; then cool down to 590℃ at 15℃ / min and keep it for 1 hour; finally cool down to below 100℃ at 15℃ / min and take out of the furnace.

[0036] Step S4, using the annealed base glass plate as a physical partition between the first heating zone and the second heating zone; the base glass plate is arranged horizontally, and the first heating zone is located above the base glass plate, and the second heating zone is located below the base glass plate, so that the first heating zone and the second heating zone respectively heat treat the base glass plate from the upper and lower surface directions of the base glass plate, and then the first heating zone and the second heating zone stop heating successively to obtain lithium disilicate glass ceramics. The specific heat treatment process is: the temperature of the first heating zone and the second heating zone is first increased to 510°C and kept warm for 2h; then increased to 600°C and kept warm for 60min; then the second heating zone stops heating and cools naturally, while the first heating zone continues to keep warm for 30min; finally, the first heating zone stops heating and cools naturally.

[0037] After testing, the chemical composition of lithium disilicate glass-ceramics is: SiO2, 71.5wt%, Li2O, 14.5wt%, Al2O3, 3.5wt%, K2O, 1.1wt%, Na2O, 1.5wt%, P2O5, 3.9wt%, TiO2, 1wt%, F, 1wt%, CeO2, 0.8wt%, Er2O3, 1.1wt%, MnO2, 0.1wt%.

[0038] In this embodiment, the positions of the first heating zone and the second heating zone can also be used interchangeably as required.

[0039] Attached Figure 1 The XRD test results of the prepared lithium disilicate glass ceramics are shown in FIG. It can be clearly seen from the figure that the main crystalline phase is lithium disilicate.

[0040] Example 2

[0041] A method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color, comprising the following steps:

[0042] Step S1, weighing raw materials according to the ratio, mixing them evenly, melting them at a high temperature of 1400°C, and keeping them warm for 2 hours to obtain a homogeneous glass liquid; wherein the raw materials are composed of: quartz sand 56.08wt%, lithium carbonate 28.29wt%, aluminum hydroxide 4.22wt%, potassium carbonate 1.16wt%, sodium carbonate 1.28wt%, diammonium phosphate 4.99wt%, titanium dioxide 0.79wt%, sodium fluorosilicate 1.62wt%, cerium oxide 0.63wt%, erbium oxide 0.86wt%, and manganese dioxide 0.08wt%.

[0043] Step S2, preheating the forming mold to 200°C, pouring the glass liquid into the preheated forming mold, and cooling to obtain a basic glass plate.

[0044] Step S3, placing the base glass plate in an annealing furnace for annealing treatment. The specific process of annealing treatment is: keep the temperature in the furnace at 590℃ for 1 hour; then increase the temperature to 750℃ at 3℃ / min and keep it for 2.5 hours; then increase the temperature to 830℃ at 3℃ / min and keep it for 1.5 hours; then increase the temperature to 910℃ at 15℃ / min and keep it for 1 hour; then cool down to 590℃ at 15℃ / min and keep it for 1 hour; finally cool down to below 100℃ at 15℃ / min and take out of the furnace.

[0045] Step S4, using the annealed base glass plate as a physical partition between the first heating zone and the second heating zone; the base glass plate is arranged horizontally, and the first heating zone is located above the base glass plate, and the second heating zone is located below the base glass plate, so that the first heating zone and the second heating zone respectively heat treat the base glass plate from the upper and lower surface directions of the base glass plate, and then the first heating zone and the second heating zone stop heating successively to obtain lithium disilicate glass ceramics. The specific heat treatment process is: the temperature of the first heating zone and the second heating zone is first increased to 550°C and kept warm for 1h; then increased to 720°C and kept warm for 10min; then the second heating zone stops heating and cools naturally, while the first heating zone continues to keep warm for 60min; finally, the first heating zone stops heating and cools naturally.

[0046] After testing, the chemical composition of lithium disilicate glass-ceramics is: SiO2, 71.5wt%, Li2O, 14.5wt%, Al2O3, 3.5wt%, K2O, 1.1wt%, Na2O, 1.5wt%, P2O5, 3.9wt%, TiO2, 1wt%, F, 1wt%, CeO2, 0.8wt%, Er2O3, 1.1wt%, MnO2, 0.1wt%.

[0047] Example 3

[0048] A method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color, comprising the following steps:

[0049] Step S1, weighing raw materials according to the ratio, mixing them evenly, melting them at a high temperature of 1400°C, and keeping them warm for 2 hours to obtain a homogeneous glass liquid; wherein the raw materials are composed of: 56.08wt% of quartz sand, 28.29wt% of lithium carbonate, 4.22wt% of aluminum hydroxide, 1.16wt% of potassium carbonate, 1.28wt% of sodium carbonate, 4.99wt% of diammonium phosphate, 0.79wt% of titanium dioxide, 1.62wt% of sodium fluorosilicate, 0.63wt% of cerium oxide, 0.86wt% of erbium oxide, and 0.08wt% of manganese dioxide.

[0050] Step S2, preheating the forming mold to 200°C, pouring the glass liquid into the preheated forming mold, and cooling to obtain a basic glass plate.

[0051] Step S3, placing the base glass plate in an annealing furnace for annealing treatment. The specific process of annealing treatment is: keep the temperature in the furnace at 590℃ for 1 hour; then increase the temperature to 750℃ at 3℃ / min and keep it for 2.5 hours; then increase the temperature to 830℃ at 3℃ / min and keep it for 1.5 hours; then increase the temperature to 910℃ at 15℃ / min and keep it for 1 hour; then cool down to 590℃ at 15℃ / min and keep it for 1 hour; finally cool down to below 100℃ at 15℃ / min and take out of the furnace.

[0052] Step S4, using the annealed base glass plate as a physical partition between the first heating zone and the second heating zone; the base glass plate is arranged horizontally, and the first heating zone is located above the base glass plate, and the second heating zone is located below the base glass plate, so that the first heating zone and the second heating zone respectively heat treat the base glass plate from the upper and lower surface directions of the base glass plate, and then the first heating zone and the second heating zone stop heating successively to obtain lithium disilicate glass ceramics. The specific heat treatment process is: the temperature of the first heating zone and the second heating zone is first increased to 530°C and kept warm for 1.5h; then increased to 660°C and kept warm for 35min; then the second heating zone stops heating and cools naturally, while the first heating zone continues to keep warm for 45min; finally, the first heating zone stops heating and cools naturally.

[0053] After testing, the chemical composition of lithium disilicate glass-ceramics is: SiO2, 71.5wt%, Li2O, 14.5wt%, Al2O3, 3.5wt%, K2O, 1.1wt%, Na2O, 1.5wt%, P2O5, 3.9wt%, TiO2, 1wt%, F, 1wt%, CeO2, 0.8wt%, Er2O3, 1.1wt%, MnO2, 0.1wt%.

[0054] Example 4

[0055] A method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color, comprising the following steps:

[0056] Step S1, weighing raw materials according to the ratio, mixing them evenly, melting them at a high temperature of 1400°C, and keeping them warm for 2 hours to obtain a homogeneous glass liquid; wherein the raw materials are composed of: 50.33wt% quartz sand, 29.43wt% lithium carbonate, 2.55wt% aluminum hydroxide, 4.17wt% potassium carbonate, 2.57wt% diammonium phosphate, 0.79wt% titanium oxide, 4.88%wt sodium fluorosilicate, 1.19wt% cerium oxide, 3.93wt% erbium oxide, and 0.16wt% manganese dioxide.

[0057] Step S2, preheating the forming mold to 200°C, pouring the glass liquid into the preheated forming mold, and cooling to obtain a basic glass plate.

[0058] Step S3, placing the base glass plate in an annealing furnace for annealing treatment. The specific process of annealing treatment is: keep the temperature in the furnace at 590℃ for 1 hour; then increase the temperature to 750℃ at 3℃ / min and keep it for 2.5 hours; then increase the temperature to 830℃ at 3℃ / min and keep it for 1.5 hours; then increase the temperature to 910℃ at 15℃ / min and keep it for 1 hour; then cool down to 590℃ at 15℃ / min and keep it for 1 hour; finally cool down to below 100℃ at 15℃ / min and take out of the furnace.

[0059] Step S4, using the annealed base glass plate as a physical partition between the first heating zone and the second heating zone; the base glass plate is arranged horizontally, and the first heating zone is located above the base glass plate, and the second heating zone is located below the base glass plate, so that the first heating zone and the second heating zone respectively heat treat the base glass plate from the upper and lower surface directions of the base glass plate, and then the first heating zone and the second heating zone stop heating successively to obtain lithium disilicate glass ceramics. The specific heat treatment process is: the temperature of the first heating zone and the second heating zone is first increased to 530°C and kept warm for 1.5h; then increased to 660°C and kept warm for 35min; then the second heating zone stops heating and cools naturally, while the first heating zone continues to keep warm for 45min; finally, the first heating zone stops heating and cools naturally.

[0060] After testing, the chemical composition of lithium disilicate glass-ceramics is: SiO2, 66.52wt%, Li2O, 15wt%, Al2O3, 2.1wt%, K2O, 3.58wt%, Na2O, 0.1wt%, P2O5, 2wt%, TiO2, 1wt%, F, 3wt%, CeO2, 1.5wt%, Er2O3, 5wt%, MnO2, 0.2wt%.

[0061] Example 5

[0062] A method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color, comprising the following steps:

[0063] Step S1, weighing raw materials according to the ratio, mixing them evenly, melting them at a high temperature of 1400°C, and keeping them warm for 2 hours to obtain a homogeneous glass liquid; wherein the raw materials are composed of: quartz sand 60.66wt%, lithium carbonate 26.27wt%, aluminum hydroxide 2.63wt%, potassium carbonate 2.26wt%, ammonium dihydrogen phosphate 2.65wt%, titanium oxide 1.63wt%, sodium fluorosilicate, 2.51%wt, cerium oxide 0.82wt%, erbium oxide 0.41wt%, and manganese dioxide 0.16wt%.

[0064] Step S2, preheating the forming mold to 200°C, pouring the glass liquid into the preheated forming mold, and cooling to obtain a basic glass plate.

[0065] Step S3, placing the base glass plate in an annealing furnace for annealing treatment. The specific process of annealing treatment is: keep the temperature in the furnace at 590℃ for 1 hour; then increase the temperature to 750℃ at 3℃ / min and keep it for 2.5 hours; then increase the temperature to 830℃ at 3℃ / min and keep it for 1.5 hours; then increase the temperature to 910℃ at 15℃ / min and keep it for 1 hour; then cool down to 590℃ at 15℃ / min and keep it for 1 hour; finally cool down to below 100℃ at 15℃ / min and take out of the furnace.

[0066] Step S4, using the annealed base glass plate as a physical partition between the first heating zone and the second heating zone; the base glass plate is arranged horizontally, and the first heating zone is located above the base glass plate, and the second heating zone is located below the base glass plate, so that the first heating zone and the second heating zone respectively heat treat the base glass plate from the upper and lower surface directions of the base glass plate, and then the first heating zone and the second heating zone stop heating successively to obtain lithium disilicate glass ceramics. The specific heat treatment process is: the temperature of the first heating zone and the second heating zone is first increased to 530°C and kept warm for 1.5h; then increased to 660°C and kept warm for 35min; then the second heating zone stops heating and cools naturally, while the first heating zone continues to keep warm for 45min; finally, the first heating zone stops heating and cools naturally.

[0067] After testing, the chemical composition of lithium disilicate glass-ceramics is: SiO2, 75wt%, Li2O, 13wt%, Al2O3, 2.1wt%, K2O, 1.89wt%, Na2O, 0.81wt%, P2O5, 2wt%, TiO2, 2wt%, F, 1.5%wt, CeO2, 1wt%, Er2O3, 0.5wt%, MnO2, 0.2wt%.

[0068] Example 6

[0069] In this embodiment, the same raw material composition and preparation method as in Example 1 are used to process the denture, the difference being that the glass liquid is cast into the denture forming mold to obtain the corresponding blank, which is then annealed and heat treated.

[0070] Figure 2 The appearance of the denture produced is shown in FIG. Figure 2 As shown in the figure, the denture is slightly yellow throughout; the cutting end is translucent, with high transparency and relatively light color, while the cervical edge has low transparency and relatively dark color, forming a natural gradient effect with increasing transparency and lighter color from the cervical edge to the cutting end. Figure 3The SEM test results of the incisal edge of the prepared denture are shown in Figure 2. Figure 4 The following is the SEM test result of the cervical edge of the prepared denture. Figure 3 and attached Figure 4 It can be seen that the grain size at the cutting end is significantly larger than that at the neck edge.

Claims

1. A method for preparing lithium disilicate glass ceramics with gradient transparency and color, characterized in that: The following steps are involved: Step S1, weighing raw materials according to the ratio, mixing them evenly and then melting them at high temperature to obtain homogeneous glass liquid; Step S2, pouring the glass liquid into a preheated forming mold and cooling it to obtain a basic glass plate; Step S3, placing the base glass plate in an annealing furnace for annealing treatment; Step S4, using the annealed base glass plate as a physical partition between the first heating zone and the second heating zone, and heat-treating the base glass plate from the two side surfaces of the base glass plate by the first heating zone and the second heating zone respectively, and then stopping heating in the first heating zone and the second heating zone successively to obtain lithium disilicate glass ceramics with layered gradient transparency and color.

2. The method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color according to claim 1, characterized in that: The chemical composition of the lithium disilicate glass-ceramic obtained in the step S4 is: SiO2, 65~75wt%, Li2O, 13~15wt%, Al2O3, 2~5wt%, K2O, 0.1~4wt%, Na2O, 0.1~4wt%, P2O5, 2~5wt%, TiO2, 1~4wt%, F, 0.5~3wt%, CeO2, 0.5~2wt%, Er2O3, 0.1~5wt%, MnO2, 0.1~1wt%.

3. The method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color according to claim 1, characterized in that: The temperature of the high temperature melting in step S1 is 1350-1450° C. and the temperature is kept for 1-4 hours.

4. The method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color according to claim 1, characterized in that: The preheating temperature of the molding die in step S2 is 100-800°C.

5. The method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color according to claim 1, characterized in that: The specific process of annealing treatment in step S3 is: keep the temperature in the furnace at 520-650°C for 0.5-2h; then heat to 720-780°C at ≤5°C / min, and keep it for 0.5-4h; then heat to 820-850°C at ≤5°C / min, and keep it for 0.5-2h; then heat to 900-920°C at 15-20°C / min, and keep it for 0.5-1h; then cool to 520-650°C at 15-20°C / min, and keep it for 0.5-2h; finally cool to below 100°C at 15-20°C / min and take out of the furnace.

6. The method for preparing a lithium disilicate glass ceramic with gradient transparency and color according to any one of claims 1 to 4, characterized in that: When the first heating zone and the second heating zone perform heat treatment on the base glass plate from the two side surfaces of the base glass plate in step S4, the temperatures of the first heating zone and the second heating zone are first raised to the same preset temperature and kept warm; then the first heating zone stops heating and cools naturally, while the second heating zone continues to keep warm; finally, the second heating zone stops heating and cools naturally; Alternatively, when the first heating zone and the second heating zone perform heat treatment on the base glass plate from both side surfaces of the base glass plate in step S4, the temperatures of the first heating zone and the second heating zone are first raised to the same preset temperature and kept warm; Then the second heating zone stops heating and cools naturally, while the first heating zone continues to keep warm; finally the first heating zone stops heating and cools naturally.

7. The method for preparing the lithium disilicate glass ceramics with gradual changes in transparency and color according to claim 6, characterized in that: In step S4, the temperatures of the first heating zone and the second heating zone are raised to 510-720° C. and kept warm for 1-3 hours; then the second heating zone stops heating, while the first heating zone continues to keep warm for 30-60 minutes before stopping heating.

8. The method for preparing lithium disilicate glass ceramics with layered and gradient transparency and color according to claim 7, characterized in that: In the step S4, the temperature of the first heating zone and the second heating zone is first increased to 510-550° C. and kept for 1-2 hours; and then increased to 600-720° C. and kept for 10-60 minutes.

9. The method for preparing lithium disilicate glass ceramics with gradient transparency and color according to claim 6, characterized in that: In step S4, the temperatures of the first heating zone and the second heating zone are raised to 510-720° C. and kept warm for 1-3 hours; then the first heating zone stops heating, while the second heating zone continues to keep warm for 30-60 minutes before stopping heating.

10. The method for preparing lithium disilicate glass ceramics with gradient transparency and color according to claim 9, characterized in that: In the step S4, the temperature of the first heating zone and the second heating zone is first increased to 510-550° C. and kept for 1-2 hours; and then increased to 600-720° C. and kept for 10-60 minutes.